The Theme of the Body in the Novel “El-Zendjia” by Aisha Bannour - Bouzerda, Meriem; Bouksiba, Safia; Annouche, Amina (Journal of Human Sciences, 2025)
The feminist novel has made significant strides in highlighting gender issues and roles, as its themes have multiplied, and its methods and styles of presentation have diversified. The theme of the body and its representations has become one of the most prominent topics in Arabic novels in general and Algerian literature in particular, where it has formed the central focus of artistic works in both vision and representation. This study aims to uncover the various cultural perceptions and implicit systems underlying the representations of the female body under the dominance of a patriarchal society, as portrayed in the narrative turns of the novel "Al-Zandjia" by Aisha Benour.